PENETAPAN UPAH MINIMUM KOTA PALEMBANG TAHUN 2016 DALAM PERSPEKTIF EKONOMI SYARI'AH - Hana Pertiwi (Medina-te : Jurnal Studi Islam, 2017)
Islam commands people to seek a job in meeting the needs of life, in way can benefit those who seek. in this research is the study subject “ minimum wage in the city of palembang in 2016 sharia economic perspective” the formulation of the problem how the principles remuneration according to shariah economics, how the mecanism for setting the minimum wage the city of palembang in accordance with economic prinsiple, and what are the implications for the welfare of the city minimum wage workers in the city of Palembang. This research is a field research, which was conducted using qualitative. The source of this study are primari and secondary. Techniques in this study is observation, interview and documentation. The method used in this research is normative juridical approach that is supported by empirical juridical approach.